Design of a highly potent HIV-1 fusion inhibitor targeting the gp41 pocket. (2nd January 2015) - Chong, Huihui; Qiu, Zonglin; Su, Yang; Yang, Lingli; He, Yuxian
Abstract : Objective: T20 (Enfuvirtide), which is a 36-residue peptide derived from the C-terminal heptad repeat (CHR) of gp41, is the only clinically available HIV-1 fusion inhibitor, but it easily induces drug resistance, which calls for next-generation drugs. Design: We recently demonstrated that the M-T hook structure can be used to design a short CHR peptide that specifically targets the conserved gp41 pocket rather than the T20-resistant sites. We attempted to develop more potent HIV-1 fusion inhibitors based on the structure–activity relationship of MT-SC22EK. Methods: Multiple biophysical and functional approaches were performed to determine the structural features, binding affinities and anti-HIV activities of the inhibitors. Results: The 23-residue peptide HP23, which mainly contains the M-T hook structure and pocket-binding sequence, showed a helical and trimeric state in solution. HP23 had dramatically improved binding stability and antiviral activity, and it was the most potent inhibitor of the M-T hook-modified and unmodified control peptides. More promisingly, HP23 was highly active in the inhibition of diverse HIV-1 subtypes, including T20 and MT-SC22EK resistant HIV-1 mutants, and it exhibited a high genetic barrier to the development of resistance. Conclusion: Our studies delivered an ideal HIV-1 fusion inhibitor that specifically targeted the highly conserved gp41 pocket and possessed potent binding and antiviral activity. Furthermore, HP23 can serve as a critical tool to explore the mechanisms of HIV-1 fusion and inhibition. Abstract : Supplemental Digital Content is available in the text